PERBANDINGAN TOKSISITAS ANTARA EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura) DAN DAUN KAPAS (Gossypium hirsutum) TERHADAP LARVA UDANG (Artemia Salina Leach) DENGAN METODE BSLT (Brine Shrimp Lethality Test) - Mega Pratiwi Irawan; Alfin Surya (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Gossypium hirsutum cotton is a member of the Malvaceae family, and its seeds and leaves have been widely used for health care. G. hirsutum cotton has secondary metabolites in the form of flavonoids, tannins, saponins and steroids that can provide pharmacological effects. This study aims to determine the comparison of the toxicity between the ethanol extract of cherry leaves (Muntingia calabura) and cotton leaves (Gossypium hirsutum) using the BSLT (Brine Shrimp Lethality Test) method. The extract was made by maceration method using 96% ethanol as solvent. This toxicity test was carried out using 48 hours old Artemia salina L. shrimp larvae. The results of this study were analyzed using a probit table with the LC50 value of the ethanolic extract of cherry leaves, which was 100 ppm, while the LC50 value of the ethanolic extract of cotton leaves was 158 ppm. This indicates that the extract is highly toxic to the mortality test of Artemia salina L. larvae